2016
DOI: 10.1084/jem.20160833
|View full text |Cite
|
Sign up to set email alerts
|

Unique pathological tau conformers from Alzheimer’s brains transmit tau pathology in nontransgenic mice

Abstract: Intracerebral inoculation of tau fibrils from AD brains results in the induction and propagation of tau inclusions in WT mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

40
499
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 345 publications
(568 citation statements)
references
References 61 publications
40
499
0
1
Order By: Relevance
“…However, it is likely that tau aggregates within brain lysate have higher seeding potencies than recombinant tau fibrils (54). Indeed the cerebral injection of human tauopathy brain lysates can induce local tau pathology, or pathology that spreads along connected brain regions, in non-transgenic mice (33,66).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is likely that tau aggregates within brain lysate have higher seeding potencies than recombinant tau fibrils (54). Indeed the cerebral injection of human tauopathy brain lysates can induce local tau pathology, or pathology that spreads along connected brain regions, in non-transgenic mice (33,66).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is likely that tau aggregates within brain lysate have higher seeding potencies than recombinant tau fibrils (54). Indeed the cerebral injection of human tauopathy brain lysates can induce local tau pathology, or pathology that spreads along connected brain regions, in non-transgenic mice (33,66).We showed that aggregated P301L tau failed to sequester soluble WT tau into insoluble aggregates when co-expressed in the HEK293T seeding model, demonstrating that even when intracellular tau aggregates are generated, WT tau is resilient to recruitment into inclusions. Given that there seemed to be less aggregation of P301L tau in the presence of WT tau expression, it is plausible that WT tau may reduce templated conformation of P301L tau.…”
mentioning
confidence: 83%
“…Seeding of human tau from homogenates of AD and tauopathies with neuronal and glial components is also observed after inoculation into the brain of wild-type mice [178,179].…”
Section: Disease Progression: Seeding and Spreading; Role Of Astrocytesmentioning
confidence: 93%
“…While seeding aggregation with AD brainderived PHFs has been reported in vitro for recombinant Tau (22,23), as well as in vivo (24)(25)(26), it still does not answer whether phosphorylation can drive the initial nucleation of fibers.…”
mentioning
confidence: 99%